HUBUNGAN SIKAP KERJA, PENCAHAYAAN DAN SUHU TERHADAP KELELAHAN KERJA DAN KELELAHAN MATA PADA PENJAHIT DI KAMPUNG SOLOR KUPANG 2017 - Kristina Dede Odi; Sintha Lisa Purimahua; Luh Putu Ruliati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
The discomfort of work environment which is caused by temperature will affect a worker to complete his or her job. For lack of attention to work place adjusment, position, and work equipment will certanly cause problems dealing with occupational desease. Job that have a need of accuracy without unequal to lighting, have the impact to eye fatigue. This study was aimed to find out the relationship of attitude to work, lighting, and temperature towards work fatigue and eye fatigue at tailors in Kampung Solor Kupang 2017. The type of this research was an analytic survey with cross sectional approach. The number of population was 34 tailors with the total sample 34 tailors who spread in 16 of stitch. In analising the data, the researcher used chi square with significant correlation to work fatigue, p value =0,011. Work attitude had significant correlation to eye fatigue with p value=0,037, lighting had no significant correlation to work fatigue with p value=0,683, lighting had correlation with eye fatigue p value =0,045, temperature had significant relation to work fatigue by p value=0,023 and it had no correlation to eye fatigue by p value =0,106.